The day tripper : a novel - Goodhand, James (Mira, 2024)
In 1995, Alex Dean has a perfect life ahead of him, but he ends up bruised, bloody, and almost drowned in a river. He awakes to find it is now 2010 or 2015 or 1999, and he must piece his life back together.